Surgiflo® hemostatic matrix versus NasoPore® nasal packing following postassium titanyl phosphate laser surgery for hereditary hemorrhagic telangiectasia: A randomized controlled trial. Issue 2 (21st March 2023) - Pyne, Justin M.; Murray, Scott; Kelly, Brendan C.; Song, Jin Soo; Rosvall, Brandon R.; Côté, David W. J.
Abstract: Background: To help ensure adequate hemostasis immediately following potassium titanyl phosphate (KTP) laser treatment, many centres treating hereditary hemorrhagic telangiectasia (HHT) routinely use nasal packing post‐operatively. The purpose of this study was to compare hemostatic thrombin matrix with standard packing for postoperative bleeding, patient pain, and comfort. Methods: A prospective, randomized, double‐blinded, non‐inferiority study was conducted with participants at an HHT centre of excellence (COE) and randomized to the treatment group with reconstituted thrombin gelatin matrix (Surgiflo®) or control group with a biodegradable synthetic polyurethane foam (NasoPore®). Adult subjects with confirmed HHT and moderate to severe epistaxis (a minimum calculated epistaxis severity score [ESS] of 4.0) warranting KTP laser treatment were recruited. Data was collected 2 weeks post operatively by a blinded reviewer completing a visual outcomes evaluation and each patient completing a subjective symptoms questionnaire. Non‐parametric statistical analysis was employed. Results: Twenty‐eight adult patients were randomized to the treatment and control arms with comparable preoperative epistaxis severity scores. Postoperative nasal bleeding was equivalent. Significantly less pain was found in the treatment arm ( p  = .005). While there were trends towards less obstruction and increased satisfaction in the treatment group as well as less crusting in the control group, these findings were not statistically significant. Allocation to the treatment group was associated with an approximately $75 higher cost. Conclusions: When compared to NasoPore® for hemostasis, Surgiflo® hemostatic matrix performed equivalently while causing less discomfort in HHT patients following nasal KTP treatment. Level of evidence: 1b. Abstract : This article compares the degree of pain and comfort of a two types of nasal packing for patients with hereditary hemorrhagic telangiectasia who have undergone laser surgery for recurrent epistaxis. The results indicate that the Surgiflo® material is less painful and as effective as the NasoPore® material.